A protestáns gregoriánum utóélete az erdélyi kortárs egyházzenei életben - KURTA, József Tibor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The Afterlife of Protestant Gregorian Chant in Contemporary Transylvanian Church Music. The loss of the genre of Protestant Gregorian chant did not mean the complete disappearance of Gregorian chant from the life of the Protestant churches in Transylvania. Many Gregorian songs and melodies were transferred to later congregational hymnbooks. In places where the religious community demanded it, the singing of the Passion and Lamentation continued. This was the case in several parishes where the Holy Week liturgy were still sung in the 20th century. In most cases, the place, time, and scope of the lecture changed, but it was essentially for the same purpose and, dare we say it, with the same benefit. The research of Gregorian chant, and within it of Protestant Gregorian chant in Hungary and Transylvania, has had a significant result: these vocal movements have begun to be heard live. Partly in their place, in liturgical settings, in churches, and partly in performances, presentations, with a change of function, with the intention of popularization. In the following, without claiming to be exhaustive, I will describe the major Transylvanian Gregorian choirs, whose chant repertoire included Protestant Gregorian chant movements, and the major events in which this liturgical practice was performed.